Applications of Medial Sural Perforator Free Flap for Head and Neck Reconstructions - Choi, Jong Woo; Nam, Soon Yuhl; Choi, Seung Ho; Roh, Jong Lyel; Kim, Sang Yoon; Hong, Joon Pio (Journal of Reconstructive Microsurgery, 2013)
Oropharyngeal defects left after tumor resection are usually reconstructed with radial forearm or anterolateral thigh (ALT) perforator free flaps, but these flaps can be too thin or too thick. In this study, medial sural perforator free flaps with intermediate volumes were used for oropharyngeal reconstruction. Of the 243 patients with oropharyngeal cancer who underwent head and neck reconstruction between October 2006 and October 2011, the medial sural perforator free flap was used 20 times. The number and locations of the main sizable perforators, the dimensions and thickness of the flap, and the length of the pedicle were recorded. Satisfactory results were achieved in 18 patients. The flaps in the two remaining cases failed. The vertical locations of the main sizable medial sural perforators were 6 to 15 cm away from the popliteal crease. The medial sural perforator free flaps ranged from 4 to 10 mm in thickness. Medial sural perforator free flaps may be an alternative for medium-sized defects that cannot be properly reconstructed with radial forearm or ALT perforator free flaps because of their inappropriate flap volume.
Keywords: medial sural; medial sural perforator flap; perforator flap; oropharyngeal reconstruction; head and neck reconstruction